Complejo ecoturístico como elemento articulador al sur del departamento del Huila (2022)
In the following work of degree of architectural approach, an identification of the most representative tourist places of the department of Huila is disclosed, with the objective of solving a tourist problem in the south of the department, due to the waste of the tourist impact that exists between the municipality of Suaza and Florencia (Caquetá), a connection with great tourism potential which will be a catalyst for future social and tourism projects in the region, thus attracting greater economic growth for the community and, in the same way, national recognition. for the municipality, with guidelines to develop an ecotourism complex that architecturally represents the materials of the area, where indigenous construction systems of the region are implemented, with the methodological plus of permaculture and rainwater harvesting, the culture of the region and sustainable development, as a result of the exponential growth that has sitting in the department of Huila in recent years.